Crystalline phase of TiO2 nanotube arrays on Ti–35Nb–4Zr alloy: Surface roughness, electrochemical behavior and cellular response. Issue 4 (15th February 2022) - Fatichi, Alberto Z.; de Mello, Mariana G.; Pereira, Karina D.; Antonio, Luísa G.M.; Luchessi, Augusto D.; Caram, Rubens; Cremasco, Alessandra
Abstract: An investigation was made into the electrochemical, structural and biological properties of self-organized amorphous and anatase/rutile titanium dioxide (TiO2 ) nanotubes deposited on Ti–35Nb–4Zr alloy through anodization-induced surface modification. The surface of as-anodized and heat-treated TiO2 nanotubes was analyzed by field emission scanning electron microscopy (FE-SEM), revealing morphological parameters such as tube diameter, wall thickness and cross-sectional length. Glancing angle X-ray diffraction (GAXRD) was employed to identify the structural phases of titanium dioxide, while atomic force microscopy (AFM) was used to measure surface roughness associated with cell interaction properties. The electrochemical stability of TiO2 was examined by electrochemical impedance spectroscopy (EIS) and the results obtained were correlated with the microstructural characterization. The in vitro bioactivity of as-anodized and crystallized TiO2 nanotubes was also analyzed as a function of the presence of different TiO2 polymorphic phases. The results indicated that anatase TiO2 showed higher surface corrosion resistance and greater cell viability than amorphous TiO2, confirming that TiO2 nanotube crystallization plays an important role in the material's electrochemical behavior and biocompatibility.